Fibroblast-myofibroblast transition is differentially regulated by bronchial epithelial cells from asthmatic children. Issue 1 (December 2015) - Reeves, Stephen; Kolstad, Tessa; Lien, Tin-Yu; Herrington-Shaner, Sarah; Debley, Jason
Abstract Background Airway remodeling is a proposed mechanism that underlies the persistent loss of lung function associated with childhood asthma. Previous studies have demonstrated that human lung fibroblasts (HLFs) co-cultured with primary human bronchial epithelial cells (BECs) from asthmatic children exhibit greater expression of extracellular matrix (ECM) components compared to co-culture with BECs derived from healthy children. Myofibroblasts represent a population of differentiated fibroblasts that have greater synthetic activity. We hypothesized co-culture with asthmatic BECs would lead to greater fibroblast to myofibroblast transition (FMT) compared to co-culture with healthy BECs. Methods BECs were obtained from well-characterized asthmatic and healthy children and were proliferated and differentiated at an air-liquid interface (ALI). BEC-ALI cultures were co-cultured with HLFs for 96 hours. RT-PCR was performed in HLFs for alpha smooth muscle actin (α-SMA) and flow cytometry was used to assay for α-SMA antibody labeling of HLFs. RT-PCR was also preformed for the expression of tropomyosin-I as an additional marker of myofibroblast phenotype. In separate experiments, we investigated the role of TGFβ2 in BEC-HLF co-cultures using monoclonal antibody inhibition. Results Expression of α-SMA by HLFs alone was greater than by HLFs co-cultured with healthy BECs, but not different than α-SMA expression by HLFs co-cultured with asthmatic BECs. Flow cytometry also revealed significantly less α-SMA expression by healthy co-co-cultures compared to asthmatic co-cultures or HLF alone. Monoclonal antibody inhibition of TGFβ2 led to similar expression of α-SMA between healthy and asthmatic BEC-HLF co-cultures. Expression of topomyosin-I was also significantly increased in HLF co-cultured with asthmatic BECs compared to healthy BEC-HLF co-cultures or HLF cultured alone. Conclusion These findings suggest dysregulation of FMT in HLF co-cultured with asthmatic as compared to healthy BECs. Our results suggest TGFβ2 may be involved in the differential regulation of FMT by asthmatic BECs. These findings further illustrate the importance of BEC-HLF cross-talk in asthmatic airway remodeling.